2005
DOI: 10.1097/00001756-200504040-00012
|View full text |Cite
|
Sign up to set email alerts
|

A conus peptide blocks nicotinic receptors of unmyelinated axons in human nerves

Abstract: The novel alpha-conotoxin Vc1.1 is a potential analgesic for the treatment of painful neuropathic conditions. In the present study, the effects of Vc1.1 were tested on the nicotine-induced increase in excitability of unmyelinated C-fiber axons in isolated segments of peripheral human nerves. Vc1.1 in concentrations above 0.1 microM antagonized the increase in axonal excitability produced by nicotine; the maximal inhibition was observed with 10 microM. We also demonstrate immunoreactivity for alpha 3 and alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Recent studies of ␣-conotoxins Vc1.1 and RgIA have also attributed the acute analgesia produced by these conotoxins to the antagonism of ␣9␣10 nAChRs Vincler et al, 2006;Vincler and McIntosh, 2007). However, given that Vc1.1, but not vc1a or its analog [P6O]Vc1.1, was able to inhibit a vascular response to pain and reduce chronic pain in several animal models of human neuropathy (Livett et al, 2002(Livett et al, , 2006Lang et al, 2005), it is highly unlikely that ␣9␣10 nAChRs are the molecular mechanism or therapeutic target of Vc1.1 for the treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of ␣-conotoxins Vc1.1 and RgIA have also attributed the acute analgesia produced by these conotoxins to the antagonism of ␣9␣10 nAChRs Vincler et al, 2006;Vincler and McIntosh, 2007). However, given that Vc1.1, but not vc1a or its analog [P6O]Vc1.1, was able to inhibit a vascular response to pain and reduce chronic pain in several animal models of human neuropathy (Livett et al, 2002(Livett et al, , 2006Lang et al, 2005), it is highly unlikely that ␣9␣10 nAChRs are the molecular mechanism or therapeutic target of Vc1.1 for the treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic Vc1.1 is a competitive antagonist of neuronal nAChRs in bovine adrenal chromaffin cells (Clark et al, 2006) and is most potent at recombinant ␣9␣10 nAChRs expressed in X. laevis oocytes (Vincler et al, 2006). Vc1.1 also antagonizes the nicotine-induced increase in axonal excitability of unmyelinated C-fiber axons in isolated segments of peripheral human nerves (Lang et al, 2005). Inhibition of nAChRs on unmyelinated peripheral sympathetic and/or sensory axons may alleviate pain associated with small-fiber neuropathies.…”
mentioning
confidence: 99%
“…Recovery of nerve function retained Nevin et al, 2007 Rg1A Partially reverses mechanical allodynia in several neuropathic models after intramuscular dosing. human sural nerve to nicotine (Lang et al, 2005). Vc1.1 has relatively low affinity for ␣3␤2 and ␣3␤4 nAChRs (Clark et al, 2006;Vincler and McIntosh, 2007) but may have higher affinity for more complex subunit combinations; e.g., its affinity for ␣6/␣3␣2␤2␤3 nAChRs is 140 nM (Vincler and McIntosh, 2007).…”
Section: Very Weak ␣9␣10mentioning
confidence: 99%
“…Many conotoxins are selective antagonists of a range of ion channels, transporters and membrane receptors associated with pain. Previous studies have demonstrated the analgesic potential of several different α-conotoxins that competitively inhibit neuronal nicotinic acetylcholine receptors (nAChRs) with varying degrees of subtype selectivity [2,15,24,29,36,37].…”
Section: Introductionmentioning
confidence: 99%